2009
DOI: 10.1002/cjg2.1354
|View full text |Cite
|
Sign up to set email alerts
|

Application of 20‐Moment Approximation for Ion Velocity Distribution Function in Calculations of Incoherent Scatter Spectra

Abstract: According to Grad's theory, the ion velocity distribution function is expanded to a 20‐moment approximation based on the Maxwellian distribution. The effects of the stress tensor and the heat flow vector on the ion velocity distributions are discussed. When the electric field is weak, it is reasonable to neglect the heat flow vector and the stress tensor parallel to E × B and E, respectively. The ion temperature anisotropy and asymmetry in the distribution function are caused by the stress tensor and the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The ion velocity distribution of the Maxwell molecule collision model can be obtained using the 16-moment approximation. According to Grad's theory, Xue et al [107] found that the ion velocity distribution function was expanded about a 20-moment approximation based on Maxwellian distribution. They discussed effects of the stress tensor and heat flow vector on the ion velocity distributions.…”
Section: Incoherent Scatter Spectra and Ionospheric Heating Experimentsmentioning
confidence: 99%
“…The ion velocity distribution of the Maxwell molecule collision model can be obtained using the 16-moment approximation. According to Grad's theory, Xue et al [107] found that the ion velocity distribution function was expanded about a 20-moment approximation based on Maxwellian distribution. They discussed effects of the stress tensor and heat flow vector on the ion velocity distributions.…”
Section: Incoherent Scatter Spectra and Ionospheric Heating Experimentsmentioning
confidence: 99%